2020
DOI: 10.2147/idr.s281274
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of the Short-Term Use of Fluoroquinolone and β-Lactam Antibiotics on Mouse Gut Microbiota</p>

Abstract: Background Antibiotics play an important role in the treatment of infectious diseases. However, the overuse of antibiotics increases the spread of drug-resistant bacteria and causes dysbiosis of the intestinal microbiota. Few studies have addressed the longitudinal effects of antibiotics on the microbiome and host immunity. Materials and Methods In this study, the short-term effect of fluoroquinolone (levofloxacin) and β-lactam antibiotics (meropenem, cefoperazone/sulba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…While members of phylum Firmicutes increasingly dominated the gut microbiome, accounting for around 90% of all bacteria present, members of Bacteroidetes, Proteobacteria, Cyanobacteria, and Deferribacterota all decreased following levofloxacin treatment. These data correlate closely with a recent study which compared the differential effects of levofloxacin and a number of β-lactam antibiotics (Meropenem, cefoperazone/sulbactam, and aztreonam) on the gut microbiota, which found an increase in Firmicutes and a decrease in Bacteroidetes following levofloxacin treatment. Similarly, work by Ziegler and co-workers investigated the impact of levofloxacin on the gut microbiome in comparison to the β-lactams cefepime, piperacillin-tazobactam, and Meropenem.…”
Section: Resultssupporting
confidence: 90%
“…While members of phylum Firmicutes increasingly dominated the gut microbiome, accounting for around 90% of all bacteria present, members of Bacteroidetes, Proteobacteria, Cyanobacteria, and Deferribacterota all decreased following levofloxacin treatment. These data correlate closely with a recent study which compared the differential effects of levofloxacin and a number of β-lactam antibiotics (Meropenem, cefoperazone/sulbactam, and aztreonam) on the gut microbiota, which found an increase in Firmicutes and a decrease in Bacteroidetes following levofloxacin treatment. Similarly, work by Ziegler and co-workers investigated the impact of levofloxacin on the gut microbiome in comparison to the β-lactams cefepime, piperacillin-tazobactam, and Meropenem.…”
Section: Resultssupporting
confidence: 90%
“…However, the overuse of antibiotics has led to the emergence of drug-resistant pathogens. Since antibiotics also kill some bacteria that promote host immune function and health, dysbiosis of the gut and oral microbiome occurs [ 44 ]. The present study revealed that a plant-derived lactic acid bacterial strain, designated BM53-1, produces a water-soluble polysaccharide that inhibits the production of sticky β-glucans by S. mutans .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients are not allowed to take antibiotics, probiotics, or anti-acids, which can obviously affect gut microbiota during the trial. For patients who develop an infection that requires antibiotics during the trials, they will suspend the cycle until symptoms resolve and antibiotics have been discontinued for 2 months, which is the time for the recovery of gut microbiota after antibiotics shown by the animal study [ 30 ]. After then, they will restart that cycle from the beginning.…”
Section: Methodsmentioning
confidence: 99%